Implementasi Sistem Informasi Berbasis Web dengan Fitur Chatbot untuk Meningkatkan Layanan Konsultasi - Ainil Mardiyah; Delsi Kariman; Irfan Fadhli; Muthia Ananda; Jasril Jasril (Program Studi Pendidikan IPA Fakultas MIPA Universitas Negeri Makassar, 2025)
The purpose of this community service activity is to help schools improve their consultation services by utilizing a web-based information system equipped with a chatbot feature. Furthermore, it also digitizes consultation data management. The program implementation consists of several stages: outreach, training, system implementation, mentoring, and evaluation. After the activity was completed, there was a significant improvement in the ability of teachers and staff to manage the digital system, increased ease of consultation for parents, and improved structured data documentation. The system used also expanded the reach of consultation services without the constraints of space and time. Furthermore, it reduced the administrative burden on teachers. This system can be applied to other schools to encourage the digital transformation of educational services.